Respuesta :

Simplifying 4x2 + -24x + 4y2 + 72y = 76
Reorder the terms: -24x + 4x2 + 72y + 4y2 = 76
Solving -24x + 4x2 + 72y + 4y2 = 76
Solving for variable 'x'.
Reorder the terms: -76 + -24x + 4x2 + 72y + 4y2 = 76 + -76
Combine like terms: 76 + -76 = 0 -76 + -24x + 4x2 + 72y + 4y2 = 0
 Factor out the Greatest Common Factor (GCF), '4'. 4(-19 + -6x + x2 + 18y + y2) = 0
 Ignore the factor 4.

Subproblem 1
Set the factor '(-19 + -6x + x2 + 18y + y2)' equal to zero and attempt to solve: Simplifying -19 + -6x + x2 + 18y + y2 = 0 Solving -19 + -6x + x2 + 18y + y2 = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.
The solution to this equation could not be determined.
ACCESS MORE